2021
DOI: 10.1200/jco.2021.39.15_suppl.1504
|View full text |Cite
|
Sign up to set email alerts
|

Oncology patients’ perspectives on remote patient monitoring for COVID-19.

Abstract: 1504 Background: Oncology patients are particularly vulnerable to adverse outcomes from COVID-19 and require careful monitoring to identify early deterioration and render higher level care when indicated. Several institutions launched remote patient monitoring programs (RPMPs) to care for patients with COVID-19. We describe patients’ perspectives on a COVID-19 RPMP at a National Comprehensive Cancer Center. Methods: Adult patients who had either tested positive for COVID-19 on an outpatient microbiology test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…While using remote monitoring, patients appreciate if the intervention provides security (clinical safety net), connection (link to their clinical team), empowerment (education on the disease and symptom management), user-friendliness (ease of access to services), and continuity of care provided. However, patients show concerns about additional burden (reluctance to learn something new, lack of trust in technology, avoiding additional out-of-pocket costs) and jeopardising interpersonal connections (fear of being lost in data, losing face to face contact) [30][31][32]. Future studies might consider a core-outcome set to help reviews.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…While using remote monitoring, patients appreciate if the intervention provides security (clinical safety net), connection (link to their clinical team), empowerment (education on the disease and symptom management), user-friendliness (ease of access to services), and continuity of care provided. However, patients show concerns about additional burden (reluctance to learn something new, lack of trust in technology, avoiding additional out-of-pocket costs) and jeopardising interpersonal connections (fear of being lost in data, losing face to face contact) [30][31][32]. Future studies might consider a core-outcome set to help reviews.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…We planned to perform a randomized trial but our resources were redirected during the pandemic to remotely monitor patients with COVID-19 disease. 18,19 The patients also were predominantly White and the practice settings drew from affluent neighborhoods, which could limit the generalizability of the findings. Second, a centralized team for A 0 1 2 3 remote monitoring might be cost-prohibitive to some practices.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported feasibility of RPM for management of COVID19 patients, a relatively high degree of patient engagement, and reported ease of access to electronic and clinical assessment tools by patients [27 & ]. Oncologic patient perceptions on a RPM program for COVID19 infection were evaluated in a moderately-sized cohort of patients in a single oncologic center in the USA [28]. The program consisted of enrollment of patients with recently diagnosed COVID19 infection, daily electronic symptom assessment, distribution of pulse oximeters to a subset of high-risk patients, patient education about worsening symptoms, a team of physicians, advanced practice practitioners and nurses that assessed results of the clinical data, and a standardized response to clinical assessment.…”
Section: Telemedicine For Covid19 In Hematological Patientsmentioning
confidence: 99%